2004
DOI: 10.1158/0008-5472.can-04-0637
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of the let-7 MicroRNAs in Human Lung Cancers in Association with Shortened Postoperative Survival

Abstract: In this study, we report for the first time reduced expression of the let-7 microRNA in human lung cancers. Interestingly, 143 lung cancer cases that had undergone potentially curative resection could be classified into two major groups according to let-7 expression in unsupervised hierarchical analysis, showing significantly shorter survival after potentially curative resection in cases with reduced let-7 expression (P ‫؍‬ 0.0003). Multivariate COX regression analysis showed this prognostic impact to be indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

70
1,734
2
32

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,234 publications
(1,850 citation statements)
references
References 23 publications
70
1,734
2
32
Order By: Relevance
“…We also found that in lung cancer tissue, where let-7 levels are low, RAS protein levels are elevated relative to the NAT. In support of the significance of our findings, reduced expression of let-7 is correlated with poor prognosis, as lung cancer patients with the least let-7 expression had shorter time of survival after surgery (Takamizawa et al, 2004;Yanaihara et al, 2006). We and others subsequently showed that let-7 directly regulates multiple oncogenes, including RAS, MYC and HMGA2 (Johnson et al, 2005;Lee and Dutta, 2007;Mayr et al, 2007;Sampson et al, 2007), and promoters of cell-cycle progression, such as CDC25A, CDK6 and Cyclin D2 (Johnson et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also found that in lung cancer tissue, where let-7 levels are low, RAS protein levels are elevated relative to the NAT. In support of the significance of our findings, reduced expression of let-7 is correlated with poor prognosis, as lung cancer patients with the least let-7 expression had shorter time of survival after surgery (Takamizawa et al, 2004;Yanaihara et al, 2006). We and others subsequently showed that let-7 directly regulates multiple oncogenes, including RAS, MYC and HMGA2 (Johnson et al, 2005;Lee and Dutta, 2007;Mayr et al, 2007;Sampson et al, 2007), and promoters of cell-cycle progression, such as CDC25A, CDK6 and Cyclin D2 (Johnson et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
“…These differences can classify different tumor types and tumor grades. Certain miRNA signatures are correlated with prognosis and can potentially be used to determine the specific course of treatment (Takamizawa et al, 2004;He et al, 2005a;Lu et al, 2005;Yanaihara et al, 2006;Shell et al, 2007;Visone et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let-7a has been reported to act as a tumour suppressor in some cancer types, such as lung and colon cancer, [26][27][28] and the reduced expression levels of let-7 is correlated with poor clinical prognosis. 29 Each miRNA can potentially interact with several mRNA targets via perfect or imperfect base pairing, primarily in the 39 UTR portion. A number of target prediction algorithms relying on seed sequence pairing rules and conservational analysis have been developed to score possible recognition sites and identify putative gene targets.…”
Section: Resultsmentioning
confidence: 99%
“…Takamizawa et al [68]. observed that the expression levels of let-7 were down-regulated in lung cancer, and reduced let-7 expression was significantly associated with shortened postoperative survival, independent of disease stage.…”
Section: Mirna and Cancermentioning
confidence: 99%